2015
DOI: 10.1182/blood-2014-06-579474
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of nitric oxide production by individual platelets during adhesion in flowing blood

Abstract: • The production of NO by platelets and its possible role are controversial.• We visualize NO formed by single platelets adhering to collagen under flow conditions and show that it depends on Ca 11 and modulates adhesion.Nitric oxide (NO) exerts vasodilatatory, antiplatelet, antioxidant, and antiproliferative effects. Endothelium-derived NO has been shown to be of crucial importance in cardiovascular protection, whereas evidence that NO is synthesized by platelets and regulates platelet function is still contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 56 publications
0
25
0
Order By: Relevance
“…Thrombin and collagen might increase cGMP levels slightly involving Lyn kinase, although this has not been confirmed by other studies 1, 53. Platelet‐derived NO might contribute to sGC activation and platelet NO synthesis has recently been observed by microscopy 54. Stimulation of NO production by L‐nebivolol results in reduced thrombosis in mice,55 however, the presence of any NO‐synthase in platelets has been disputed,51, 56 indicating that NO might be released from other currently unknown sources.…”
Section: Interactions At Receptor Levelmentioning
confidence: 83%
See 1 more Smart Citation
“…Thrombin and collagen might increase cGMP levels slightly involving Lyn kinase, although this has not been confirmed by other studies 1, 53. Platelet‐derived NO might contribute to sGC activation and platelet NO synthesis has recently been observed by microscopy 54. Stimulation of NO production by L‐nebivolol results in reduced thrombosis in mice,55 however, the presence of any NO‐synthase in platelets has been disputed,51, 56 indicating that NO might be released from other currently unknown sources.…”
Section: Interactions At Receptor Levelmentioning
confidence: 83%
“…1,53 Platelet-derived NO might contribute to sGC activation and platelet NO synthesis has recently been observed by microscopy. 54 Stimulation of NO production by L-nebivolol results in reduced thrombosis in mice, 55 however, the presence of any NO-synthase in platelets has been disputed, 51,56 indicating that NO might be released from other currently unknown sources. Crossactivation of cGMP production by platelet activators like VWF has 57 Similarly, platelets from patients lacking sGC expression do not aggregate well in response to low ADP concentrations, and platelet adhesion to collagen and VWF is attenuated.…”
Section: No and Sgcmentioning
confidence: 99%
“…The intensification of the signal was dependent on the presence of the NOS substrate (L-arginine), as well as of the competitive NOS inhibitor (L-NMMA). Despite the low concentrations of nitric oxide produced in platelets (compared to the endothelial cells) [82], it appears to have an important role in the aggregation of thrombocytes. According to Tymvios et al, platelet aggregation is regulated by endogenous NO.…”
Section: Nos Pathway In Platelets (Figure 4)mentioning
confidence: 97%
“…Subjects to doubt were, among others, contamination of the probes with another blood cells [77], lack of specificity of used assays [78], measurement of cGMP activity or the amount of L-citrulline as indicators of NOS activity without considering other metabolic pathways [79,80], or measurement of inorganic NO metabolites [81]. Finally, Cozzi et al directly visualized the nitric oxide production by collagen-induced platelets using an NO-specific fluorescent agent-4-amino-5-methylamino-2′,7′-difluorofluorescein diacetate (DAF-FM) [82]. This agent reacts with NO and provides a fluorescent signal.…”
Section: Nos Pathway In Platelets (Figure 4)mentioning
confidence: 99%
“…It has been found that NOS2 and NOS3 are expressed in platelets. 3 Physiologically, in an intact vasculature, circulating platelets are maintained in an inactive state by NO and prostacyclin (PGI2) released by endothelial cells lining the blood vessels. 4 NO has a significant role in the regulating vascular tone and in the controlling blood pressure.…”
Section: Introductionmentioning
confidence: 99%